Sistematização da captação e doação de órgãos e tecidos para transplante: percepções da equipe de saúde - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Objective: The objective was to know the perceptions of CIHDOTT health team about the systematization of the collection and donation of organs and tissues for transplantation. Methodology: This study is a qualitative, descriptive and exploratory field study conducted by seven health professionals from the CIHDOTT team from two hospitals in two municipalities of the western border of Rio Grande do Sul in the period from February to March 2018. Results: Based on the analysis of the research data, three categories were elaborated that permeate the systematization of organ donation and collection, one of which involves knowledge about donation and encephalic death; the second on the systematization of assistance and the third on the difficulties faced by CIHDOTT and ways of solving them. Final considerations: The study showed the perception of the professionals who are part of the CIHDOTT team regarding the pertinent aspects to the systematization of the work process regarding the donation and collection of organs and tissues for transplantation. Faced with the reality shown by the professionals, it is evident that much remains to be done in the matter of organizational arrangements, professional training and awareness of these professionals towards donor families so that the organ donation process is carried out in a safe and quality way.
Systematization of the collection and donation of organs and tissues for transplantation: perceptions of the health team
Keywords: Enfermagem; Nursing; Doação de órgãos; Transplante de órgãos; Organ donation; Organ transplantation; CNPQ::CIENCIAS DA SAUDE